Multiscale modelling of plant hormone signalling: auxin regulated lateral root emergence - Mellor, Nathan L. (2013)
The formation of lateral roots is an important post-embryonic developmental process that allows plants to adapt to their environment via exploitation of soil mineral resources. New lateral roots initiate as lateral root primordia (LRP) in the pericycle cell layer adjacent to the central vascular tissue in the primary root, and must pass through the outer cell layers of endodermis, cortex and epidermis to emerge as mature roots. A key regulator of emergence is the plant hormone auxin and it has been shown previously that in Arabidopsis the auxin induced expression of the auxin influx carrier LAX3 in specific cortical cells over LRP is required for emergence to occur, as this leads to the expression of cell wall remodelling enzymes such as polygalacturonase (PG). By developing mathematical models of auxin transport and LAX3 expression the work in the thesis aims to test the existing conceptual models for lateral root emergence, and provide testable hypotheses for the existence of additional gene regulatory components. An initial single cell model demonstrates that hysteresis and bistability may explain the experimentally observed `all-or-nothing' LAX3 spatial expression pattern in cortical cells containing a gradient of auxin concentrations. By fitting model parameters against experimental data, the model is then used to show that some auxin homeostasis mechanism is present, with both endogenous and exogenous sources of homeostasis investigated. The single cell model also investigates the validity of several alternative gene regulatory networks for LAX3, and its apparent repression by a key mediator of the auxin response, ARF19. Finally, the model is extended to a multicellular context, in which the auxin distribution from a simulated LRP source cell is used as a basis for the expression of LAX3, leading to the expression of PG in specific cells between which the LRP must pass.